AB0070 The Importance of Gliostatin as an Indicator of Disease Activity in Patients with Rheumatoid Arthritis. (10th June 2014) - Ikuta, K.; Waguri-Nagaya, Y.; Tatematsu, N.; Kawaguchi, Y.; Kobayashi, M.; Aoyama, M.; Asai, K.; Otsuka, T.
Abstract : Background: Gliostatin (GLS) plays an important role in joint destruction in rheumatoid arthritis (RA). GLS not only has an enzymatic activity as a thymidine phosphorylase but also has angiogenic and arthritogenic activities. We previously reported that GLS levels in serum and synovial fluid are increased in RA patients compared with healthy controls and in osteoarthritis patients 1 . In addition, the production of GLS by cultured RA fibroblast-like synoviocytes (FLSs) has been shown to be enhanced by IL-1β, TNF-α and GLS itself 2 . GLS levels in TNF-α-stimulated FLSs were reduced by FK506 treatment 3 . Objectives: The aim of this study was to investigate whether GLS serum levels were correlated with disease activity in RA patients. In addition we evaluated the effects of TNF inhibitors and the immunosuppressant FK506 (tacrolimus) on serum GLS levels. Methods: Serum GLS levels were measured using an enzyme immunoassay system in 146 samples from 21 Japanese RA patients. Correlations were analysed between serum GLS levels and clinical features, laboratory results and disease activity scores (DAS) as defined by EULAR. Results: We identified positive associations between serum GLS levels in RA patients and C-reactive protein (CRP), matrix metalloproteinase-3 (MMP-3), and DAS 28(ESR). After TNF inhibitor treatment for 12 months, 9 of 10 patients showed a good or moderate clinical response and also showed significant reductions in serum GLS levels and other laboratory parameters. After FK506 treatment for 12 weeks, 6 of 11 patients showed good or moderate responses, according to DAS 28(ESR), while 5 patients showed no response. Serum GLS levels and other laboratory parameters were only reduced significantly in the 6 responders. Conclusions: Circulating GLS levels were significantly associated with CRP, MMP-3, and DAS28(ESR). TNF inhibitors and FK506 may suppress serum levels of GLS and thus its angiogenic and arthritogenic activity. Our results suggested a possible role for GLS in RA pathogenesis. References: Takeuchi, et al.: Aberrant production of gliostatin/platelet-derived endothelial cell growth factor in rheumatoid arthritis. Arthritis Rheum 1994; 37: 662–72. Muro H, et al. Autocrine induction of gliostatin/platelet-derived endothelial cell growth factor (GLS/PD-ECGF) and GLS-induced expression of matrix metalloproteinases in rheumatoid arthritis synoviocytes. Rheumatol 1999; 38: 1195 -1202. Yamagami T, et al. FK506 inhibition of gliostatin/thymidine phosphorylase production induced by tumor necrosis factor-α in rheumatoid fibroblast-like synoviocytes. Rheumatol Int 2011; 37:903-909. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2315